Communicating Divine Ineffability through Paratext: How the Bible Means More than Its Words - Yarchin, William (Journal of religious and theological information, 2019)
In this article I draw attention to a non-philosophical dimension of divine ineffability communicated as religious information through paratext, defined here as visual aspects of textual presentation. I offer a case study that describes a particular paratext of divine name-substitution as it presents itself in material text platforms otherwise known as Bibles. The study covers a range of non-verbal messages offered through discrete scribal and printing practices in ancient, medieval, and modern iterations of scripture. Various graphic divine-name substitutions prompt circumscribed reading performances of the divine name. Such performances actually replace or transform the divine name, creating an apophatic disturbance in the text that communicates something fundamental about the divine which is not communicated in the Bible through the actual words of its text but through its paratext. This case study shows that inasmuch the text of the Bible has always been accompanied by paratexts, the Bible thereby means more than what its words say.